(untitled) (JURNAL IBU DAN ANAK, 2020)
ABSTRACT Background: The incidence of asphyxia neonatorum in developing countries is higher than in developed countries.Method: The study design was analytic using a cross sectional approach. All data of maternal mothers in April-December 2017 which were numbered 234 were analyzed using the chi-square formula.Results: From 82 mothers with primary caesarean section who had asphyxia were 27 infants (33%). Of the 152 secondary cesarean delivery mothers there were 47 infants with asphyxia (31%). The results of the chi-square analysis conducted, obtained a P-Value of 0.753.Conclusion: It can be concluded that there is no relationship between sectio caesarea from a midwife referral with the incidence of asphyxia neonatorum in Indrasari Rengat District Hospital.